Žemaitija ir Lietuva XIII-XVIII amžiuje: regioninės (provincinės) savivaldos spindesys ir skurdas - Saviščevas, Eugenijus (Lietuvos istorijos studijos, 2009)
This article deals with the development of Samogitia's relationship with Lithuania since the middle of the 13th century to the end of the 18th century. In the course of this period, Samogitia experienced different patterns of relationship towards Lithuania: hostile western cultural pressure in the Middle Ages; legitimate agreement on the part of Samogitians with the Lithuanian monarchy which provided for the autonomy of Samogitia in 15-16 c.; the merge of Samogitian nobles with the nobility of the Grand Duchy of Lithuania at the end of the 16 c. to 18 c. The latter merge meant the decline of the power of the regional ruling elite, having blocked the way to form a separate Samogitian political identity. All this hindered the rise of more forceful regional trends of separatism.